The financial impact of the homestay tourism in selected villages / Fennee Chong ... [et al.] - Chong, Fennee; M. Jussem, Patricia; Atan, Patrick; Mandai @ Manday, Danny Wilson (2012)
Under the One Malaysia's National Transformation Plan, the Malaysian government has envisaged the New Economic Model (NEM) aiming to improve the Rakyat's quality of life. One of the primary goals of the NEM is to achieve a higher income nation status of USD 15,000 to 20,000 per capita by 2020. Apart from that, the NEM also aims to allow all the communities to fully benefit from the wealth of the country. As Sarawak is a state with an abundance of natural resources and home to a vast array of wildlife and natural beauty, it is eager to move in tandem with the other states in Malaysia to achieve the goals set out under the NEM.